2016
DOI: 10.1007/s10096-016-2649-1
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus-associated hospitalizations over three consecutive seasons in children with congenital heart disease

Abstract: 7 days; p = 0.003). Thirteen patients (22.4 %) were admitted to the intensive care unit (ICU), for a median of 10 days. The median age at admission was 2 months, with a significant difference between HS-CHD and HNS-CHD (6 vs. 2 months; p = 0.001). The majority (97 %) of RSV-related hospitalizations occurred before 12 months of age. Patients with HS-CHD had a significantly more severe course of RSV disease and were older at the time of hospitalization. Early surgery seemed to significantly reduce the risk of RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 24 publications
(49 reference statements)
0
22
2
2
Order By: Relevance
“…CHD, irrespective of hemodynamic significance, poses a significant risk for severe RSV infection requiring hospitalization [5, 8, 2747]. RSVH rates ranged from 14 to 357 per 1000 (Table 1), although comparison of these studies is difficult as a result of differences in the study populations, some of which were not specifically CHD patients, methods used and inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CHD, irrespective of hemodynamic significance, poses a significant risk for severe RSV infection requiring hospitalization [5, 8, 2747]. RSVH rates ranged from 14 to 357 per 1000 (Table 1), although comparison of these studies is difficult as a result of differences in the study populations, some of which were not specifically CHD patients, methods used and inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…In multivariate analyses, CHD has been found to be an independent risk factor for RSVH [27, 34, 38, 50]. Data on a population of Danish children with heart disease revealed that cardiomyopathy [odds ratio (OR) 5.84, 95% CI 1.26–27.16] and HS-CHD (OR 1.53, 95% CI 1.04–2.26) were both significant predictors of RSVH [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22.4% of children were treated at the ICU; the median duration of ICU stay was 10 days (2-70 days), and the median duration of mechanical ventilation was 4 days (0-38 days). Children with hemodynamically significant disease and early heart surgery were less often hospitalized compared to those with delayed cardiac surgery [10].…”
Section: Norwood-i Palliated Hlhs Excessive Pulmonary Perfusion Via mentioning
confidence: 98%
“…& Informs clinicians and public health practitioners of changes in the pathogenicity of specific respiratory viral strains [9]. & Allows clinicians to understand disease prevalence and may indirectly guide their practice [10]. & Provides data to administrators and health planners to provide resources to support further spending for the diagnosis, characterization, and control of acute respiratory viral infections [11].…”
Section: Introductionmentioning
confidence: 99%